Effect of accelerated aging on the microhardness and color stability of flexible resins for dentures - Marcelo Coelho Goiato; Daniela Micheline dos Santos; Marcela Filie Haddad; Aldiéris Alves Pesqueira (Sociedade Brasileira de Pesquisa Odontológica, 2010)
Acrylic resins have been widely used due to their acceptable esthetics and desirable characteristics such as easy handling, good thermal conductivity, low permeability to oral fluids and color stability. Flexible resins were introduced on the market as an alternative to the use of conventional acrylic resins in the construction of complete and partial removable dentures. Although these resins present advantages in terms of esthetics and comfort, studies assessing chromatic and microhardness alterations of these materials are still scarce in the related literature. The aim of this study was to evaluate the chromatic and microhardness alterations of two commercial brands of flexible resins in comparison to the conventional resin Triplex when submitted to accelerated aging. The resins were manipulated according to manufacturers' instructions and inserted into a silicone matrix to obtain 21 specimens divided into 3 groups: Triplex, Ppflex and Valplast. Triplex presented the highest microhardness value (p < 0.05) for all the aging periods, which was significantly different from that of the other resins, followed by the values of Valplast and Ppflex. Comparison between the flexible resins (Ppflex and Valplast) revealed a statistically significant difference (p < 0.05) as regards color. The flexible resin Ppflex and the conventional resin Triplex presented no statistically significant difference (p < 0.05) as regards aging. The accelerated aging significantly increased the microhardness values of the resins, with the highest values being observed for Triplex. Valplast presented the greatest chromatic alteration after accelerated aging.